Keigo Perspective for Indonesian Migrants: A Study of Communication Challenges and Social Adaptation of Indonesian Migrants in Japan - Rahayu, Ely Triasih; Hartati; Arifiani Felayati, Safrina; Fadlullah, Fauzan (Forum for Linguistic Studies, 2025)
This study examines the barriers to communication and social adaptation, especially in the work environment that requires the use of respectful language (keigo), experienced by Indonesian migrants in Japan. These barriers greatly affect the quality of life of migrants in Japan, which needs attention from the Indonesian government, along with the increasing demand for productive age workers from Indonesia due to the demographic impact of the Japanese population. Exiting conditions show that Indonesian migrants are not only required to have technical skills, but must be able to implement keigo in the work environment. The purpose of this study is to analyses the perspectives of Indonesian migrants on keigo and the challenges they face in communication and social adaptation of Indonesian migrants' lives in Japan. In this study, qualitative methods are used to explore the experiences, perceptions, and challenges faced by Indonesian migrants in communicating and adapting to the work environment. This qualitative approach will reveal the phenomena of language, social, culture, and behaviours of migrants deeply and holistically. This phenomenological research design will focus on the subjective experiences of Indonesian migrants in using keigo and how migrants interpret the challenges and can adapt. Indonesian migrants often struggle with understanding and correctly using keigo due to its complexity and the cultural nuances involved. The ability to use keigo effectively is closely tied to social adaptation for Indonesian migrants in Japan. This study will recommend that institutions sending workers to Japan conduct simulated keigo training to create a professional workforce.